THE INFLUENCE OF SOCIAL MEDIA PLATFORMS, MARKETING TECHNIQUES AND E-COMMERCE ON CUSTOMER BUYING INTEREST IN COFFEE SHOPS PICKING IN BINJAI - Nathaly Orient; Novellyn Wigo; M. Fadhlan Mirza; Deni Faisal Mirza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to determine the extent to which social media platforms, marketing techniques, and e-commerce influence customer purchasing interest at the Kopi Petik coffee shop in Binjai, both individually and simultaneously. This study uses a quantitative approach, with data analysis using multiple linear regression. According to the analysis results, each variable partially influences customer purchasing interest. In addition, simultaneously, the three variables also show a significant influence. The coefficient of determination (R²) value is 0.727 or 72.7% of the variation in consumer purchasing interest can be explained by social media platforms, marketing techniques, and e-commerce, while the remaining 27.3% is caused by other factors not examined.